Anti-aging and anti-sticking master batch for blow molding PE and preparation method of anti-aging and anti-sticking master batch
By using specific compositions of anti-aging and anti-stick masterbatches in blow molding technology, the problem of declining performance of traditional masterbatches is solved, and the life of the finished product is extended and the convenience of use is improved.
Patent Information
- Application Number
- CN202510149373.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-04-18
AI Technical Summary
The performance of the masterbatch used in traditional blow molding declines during application, affecting the life of the finished product.
Anti-aging anti-adhesive masterbatch for blow-molded PE consisting of a carrier resin, filler, plasticizer, anti-aging agent, anti-adhesive agent, colorant, light stabilizer and antistatic agent, and the masterbatch is prepared by a specific mixing and extrusion process.
While ensuring application strength, the masterbatch has good anti-aging properties, extends the life of the finished product, and avoids bonding between the masterbatches through the installation of the anti-adhesive agent, improving the convenience of use.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of masterbatches, in particular to an anti-aging and anti-sticking masterbatch for blow molding PE and a preparation method thereof. Background Art
[0002] Blow molding is a method of manufacturing hollow thermoplastic parts. Well-known blow molding objects include bottles, barrels, cans, boxes and all containers for packaging food, beverages, cosmetics, medicines and daily necessities. Large blow-molded containers are usually used for packaging chemical products, lubricants and bulk materials. Other blow-molded products include balls, bellows and toys.
[0003] At present, masterbatch needs to be added to the slurry used in blow molding to improve the performance of the slurry. However, during the application process, the performance of the masterbatch in traditional technology will decline significantly with the change of time, which directly affects the life of the finished product.
[0004] To this end, the present invention provides an anti-aging and anti-sticking masterbatch for blow molding PE and a preparation method thereof to solve the above problems. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides an anti-aging and anti-sticking masterbatch for blow molding PE and a preparation method thereof, which solves the above problems.
[0006] To achieve the above purpose, the present invention is implemented through the following technical scheme: an anti-aging and anti-sticking masterbatch for blow molding PE, which is composed of the following components by weight: 40% to 60% of carrier resin, 15% to 33% of filler, 1% to 2.2% of plasticizer, 3% to 6.25% of anti-aging agent, 1.8% to 5.85% of anti-sticking agent, 1.4% to 1.8% of colorant, 2% to 3.6% of light stabilizer, and 5% to 9% of antistatic agent.
[0007] Preferably, the carrier resin is made of polyethylene.
[0008] Preferably, the filler is at least one of phenolic resin, glass fiber, hydroquinone and carbon powder.
[0009] Preferably, the plasticizer is at least one of diheptyl phthalate and dioctyl phthalate.
[0010] Preferably, the anti-aging agent is at least one of hydroquinone, coke black and titanium dioxide.
[0011] Preferably, the anti-sticking agent is at least one of talc and nano-silicone wax.
[0012] Preferably, the light stabilizer is at least one of zinc oxide and ascorbate.
[0013] Preferably, the antistatic agent is at least one of montmorillonite, polyacrylate and polyvinyl chloride.
[0014] A method for preparing an anti-aging and anti-sticking masterbatch for blow molding PE, comprising the following steps:
[0015] In the first step, the raw materials are weighed according to the weight ratio and introduced into a mixing device to mix the required raw materials;
[0016] The second step is to pour the mixed raw materials into the extruder, so that the raw materials undergo heating, plasticization and extrusion processes to form masterbatch;
[0017] The third step is to introduce the extruded masterbatch into the cooling equipment to quickly shape the masterbatch.
[0018] Beneficial Effects
[0019] The present invention provides an anti-aging and anti-sticking masterbatch for blow molding PE and a preparation method thereof. Compared with the prior art, it has the following beneficial effects:
[0020] (1) The anti-aging and anti-sticking masterbatch for blow molding PE and the preparation method thereof can ensure the application strength of the masterbatch while taking into account the overall anti-aging performance through overall coordination, thereby greatly ensuring the finished product life of the masterbatch product.
[0021] (2) The anti-aging and anti-sticking masterbatch for blow molding PE and the preparation method thereof can avoid adhesion between masterbatches by setting an anti-sticking agent, making the masterbatch easier to use. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Embodiment 1:
[0024] An anti-aging and anti-sticking masterbatch for blow molding PE, comprising the following components by weight: 40% to 60% of carrier resin, 15% to 33% of filler, 1% to 2.2% of plasticizer, 3% to 6.25% of anti-aging agent, 1.8% to 5.85% of anti-sticking agent, 1.4% to 1.8% of colorant, 2% to 3.6% of light stabilizer, and 5% to 9% of antistatic agent;
[0025] Furthermore, the material of the carrier resin is polyethylene, which is also called vinyl polymer resin. It is a common plastic material, which is formed by addition polymerization of ethylene monomers, and also includes a small amount of impurities, such as butadiene, hexadiene and other unsaturated hydrocarbons. Polyethylene has good mechanical strength, wear resistance, corrosion resistance and thermoplasticity, and can effectively improve the strength of the masterbatch;
[0026] In detail, the filler is at least one of phenolic resin, glass fiber, hydroquinone and carbon powder. Phenolic resin is a thermosetting synthetic resin obtained by polycondensation of phenolic monomer and polyurethane prepolymer, which can effectively improve the electrical insulation, heat resistance, corrosion resistance and wear resistance of the masterbatch;
[0027] Glass fiber is an inorganic non-metallic material, the main component of which is silicate. It is made through a series of process steps such as high-temperature melting, elongation and cooling. While ensuring the strength of the masterbatch, it can also reduce the weight of the masterbatch and improve the corrosion resistance and wear resistance of the masterbatch.
[0028] Hydroquinone has the characteristics of high efficiency and broad spectrum, and can effectively inhibit oxidation reactions, thereby protecting the masterbatch from oxidation;
[0029] Carbon powder can effectively improve the mechanical properties, stiffness and toughness of the catalog;
[0030] Further, the plasticizer is at least one of diheptyl phthalate and dioctyl phthalate, and dioctyl phthalate is an organic ester compound, which has good compatibility with most synthetic resins and rubbers used in industry except cellulose acetate and polyvinyl acetate, and has good comprehensive performance, good mixing performance, high plasticizing efficiency, low volatility, good low-temperature flexibility, water extraction resistance, high electrical properties, good heat resistance and weather resistance, so the quality of the finished product of the masterbatch can be guaranteed;
[0031] Diheptyl phthalate is a chemical substance with the molecular formula of C22H34O4. It can effectively improve the compatibility of masterbatch, and has excellent plasticizing efficiency, tensile strength and cold resistance, and can improve the quality of finished masterbatch.
[0032] Furthermore, the anti-aging agent is at least one of hydroquinone, coke black and titanium dioxide, and hydroquinone and coke black can delay the aging and degradation of the masterbatch;
[0033] Titanium dioxide is an important inorganic chemical pigment, the main component of which is titanium dioxide. Adding titanium dioxide to masterbatch can improve the heat resistance, light resistance, and weather resistance of the masterbatch product, improve the physical and chemical properties of the masterbatch product, enhance the mechanical strength of the product, and extend its service life.
[0034] In detail, the anti-sticking agent is at least one of talc and nano-silicone wax, and the talc is a magnesium silicate mineral talc family talc, the main component of which is hydrated magnesium silicate, which can increase the stability of the masterbatch shape, tensile strength, shear strength, flexural strength and pressure strength, so that the masterbatch particle size can be evenly dispersed;
[0035] Preferably, the light stabilizer is at least one of zinc oxide and ascorbate. The principle of zinc oxide shielding ultraviolet rays is absorption and scattering. Zinc oxide is an N-type semiconductor. The electrons in the valence band can accept the energy in the ultraviolet rays and undergo transitions. This is also the principle of their absorption of ultraviolet rays. The function of scattering ultraviolet rays is related to the particle size of the material. When the size is much smaller than the wavelength of ultraviolet rays, the particles can scatter the ultraviolet rays acting on them in all directions, thereby reducing the intensity of ultraviolet rays in the irradiation direction, thereby improving the anti-ultraviolet performance of the masterbatch.
[0036] Ascorbate, also known as peroxide salt, is composed of hydrogen peroxide and ascorbic acid and has the following characteristics:
[0037] 1. It can inhibit the aging process of masterbatch and extend its service life;
[0038] 2. Environmentally friendly, non-toxic, odorless and pollution-free;
[0039] 3. The effect is more lasting and reliable;
[0040] In detail, the antistatic agent is at least one of montmorillonite, polyacrylic acid salt and polyacrylic acid salt.
[0041] In summary, the anti-aging and anti-sticking masterbatch for blow molding PE can ensure the application strength of the masterbatch while taking into account the overall anti-aging performance through overall coordination, which greatly guarantees the finished product life of the masterbatch product.
[0042] Embodiment 2:
[0043] This embodiment provides a technical solution based on the first embodiment: an anti-aging and anti-sticking masterbatch for blow molding PE, which is composed of the following components by weight: 60% carrier resin, 15% filler, 2.2% plasticizer, 5.4% anti-aging agent, 4% anti-sticking agent, 1.55% colorant, 3.2% light stabilizer, and 8.65% antistatic agent;
[0044] In detail, the material of the carrier resin is polyethylene;
[0045] In this embodiment, the filler is phenolic resin and glass fiber, and is composed of the following components by weight: 50% phenolic resin and 50% glass fiber;
[0046] In this embodiment, the plasticizer is diheptyl phthalate;
[0047] In this embodiment, the anti-aging agent is coke black and titanium dioxide, and is composed of the following components by weight: 33% coke black and 67% glassy titanium dioxide;
[0048] In this embodiment, the anti-sticking agent is talcum powder and nano-silicone wax, and is composed of the following components by weight: 46% talcum powder and 54% nano-silicone wax;
[0049] In this embodiment, the light stabilizer is zinc oxide;
[0050] In this embodiment, the antistatic agent is montmorillonite and polyacrylic acid salt, and is composed of the following components by weight: 20% montmorillonite and 80% polyacrylic acid salt.
[0051] Embodiment three:
[0052] This embodiment provides a technical solution based on the first embodiment: an anti-aging and anti-sticking masterbatch for blow molding PE, which is composed of the following components by weight: 53.02% of carrier resin, 25% of filler, 1.35% of plasticizer, 5.1% of anti-aging agent, 1.43% of anti-sticking agent, 1.6% of colorant, 3.5% of light stabilizer, and 6% of antistatic agent;
[0053] In this embodiment, the filler is phenolic resin, glass fiber and carbon powder, and is composed of the following components by weight: 31.45% phenolic resin, 36.11% phenolic resin, and the rest carbon powder;
[0054] In this embodiment, the plasticizer is dioctyl phthalate;
[0055] In this embodiment, the anti-aging agent is hydroquinone and titanium dioxide, and is composed of the following components by weight: hydroquinone 36.71%, titanium dioxide 63.29%;
[0056] In this embodiment, the anti-sticking agent is talcum powder;
[0057] In this embodiment, the light stabilizer is zinc oxide and ascorbate, and is composed of the following components by weight: 45% zinc oxide and 55% ascorbate;
[0058] In this embodiment, the antistatic agent is polyacrylic acid salt and polyvinyl acid salt, and is composed of the following components by weight: polyacrylic acid salt 80%, polyvinyl acid salt 20%.
[0059] Embodiment 4:
[0060] This embodiment provides a technical solution based on the first embodiment: an anti-aging and anti-sticking masterbatch for blow molding PE, which is composed of the following components by weight: 47.42% of carrier resin, 28% of filler, 1.98% of plasticizer, 6.25% of anti-aging agent, 4.42% of anti-sticking agent, 1.73% of colorant, 3.2% of light stabilizer, and 7% of antistatic agent;
[0061] In this embodiment, the filler is phenolic resin, glass fiber and carbon powder, and is composed of the following components by weight: 38.4% phenolic resin, 53.65% carbon powder, and the rest glass fiber;
[0062] In this embodiment, the plasticizer is diheptyl phthalate and dioctyl phthalate, and is composed of the following components by weight: 77.3% diheptyl phthalate and 22.7% dioctyl phthalate;
[0063] In this embodiment, the anti-aging agent is coke black and titanium dioxide, and is composed of the following components by weight: 42.3% coke black and 57.7% titanium dioxide;
[0064] In this embodiment, the anti-sticking agent is talcum powder;
[0065] In this embodiment, the light stabilizer is zinc oxide;
[0066] In this embodiment, the antistatic agent is montmorillonite and polyacrylic acid salt, and is composed of the following components by weight: 10% montmorillonite and 90% polyacrylic acid salt.
[0067] Embodiment five:
[0068] This embodiment provides a method for preparing an anti-aging and anti-sticking masterbatch for blow molding PE on the basis of the first embodiment, and the steps are as follows:
[0069] In the first step, the raw materials are weighed according to the weight ratio and introduced into a mixing device to mix the required raw materials;
[0070] The second step is to pour the mixed raw materials into the extruder, so that the raw materials undergo heating, plasticization and extrusion processes to form masterbatch;
[0071] The third step is to introduce the extruded masterbatch into the cooling equipment to quickly shape the masterbatch.
[0072] In summary, the weight ratios of the components in Example 2, Example 3 and Example 4 are shown in the following table:
[0073] Carrier resin filler Plasticizers Anti-aging agents Anti-sticking agent Colorants Light Stabilizer Antistatic Agents Embodiment 2 60% 15% 2.2% 5.4% 4% 1.55% 3.2% 8.65% Embodiment 3 53.02% 25% 1.35% 5.1% 1.43% 1.6% 3.5% 6% Embodiment 4 47.42% 28% 1.98% 6.25% 4.42% 1.73% 3.2% 7%
[0074] After repeated tests on Example 2, Example 3 and Example 4, the aging tensile strength test data is shown in the following chart:
[0075]
[0076] As can be seen from the above diagram, embodiment 3 is the best embodiment of the present invention;
[0077] In summary, the anti-aging and anti-sticking masterbatch for blow molding PE can ensure the application strength of the masterbatch while taking into account the overall anti-aging performance through overall coordination, which greatly guarantees the finished product life of the masterbatch product.
[0078] The anti-aging and anti-sticking masterbatch for blow molding PE can avoid adhesion between masterbatches by setting an anti-sticking agent, making the masterbatch easier to use.
[0079] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0080] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0081] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An anti-aging and anti-sticking masterbatch for blow molding PE, characterized by: The invention is composed of the following components by weight: 40% to 60% of carrier resin, 15% to 33% of filler, 1% to 2.2% of plasticizer, 3% to 6.25% of anti-aging agent, 1.8% to 5.85% of anti-adhesive agent, 1.4% to 1.8% of colorant, 2% to 3.6% of light stabilizer and 5% to 9% of antistatic agent.
2. The anti-aging and anti-sticking masterbatch for blow molding PE according to claim 1, characterized in that: The material of the carrier resin is polyethylene.
3. The anti-aging and anti-sticking masterbatch for blow molding PE according to claim 1, characterized in that: The filler is at least one of phenolic resin, glass fiber, hydroquinone and carbon powder.
4. The anti-aging and anti-sticking masterbatch for blow molding PE according to claim 1, characterized in that: The plasticizer is at least one of diheptyl phthalate and dioctyl phthalate.
5. The anti-aging and anti-sticking masterbatch for blow molding PE according to claim 1, characterized in that: The anti-aging agent is at least one of hydroquinone, coke black and titanium dioxide.
6. The anti-aging and anti-sticking masterbatch for blow molding PE according to claim 1, characterized in that: The anti-sticking agent is at least one of talcum powder and nano-silicone wax.
7. The anti-aging and anti-sticking masterbatch for blow molding PE and the preparation method thereof according to claim 1, characterized in that: The light stabilizer is at least one of zinc oxide and ascorbate.
8. The anti-aging and anti-sticking masterbatch for blow molding PE according to claim 1, characterized in that: The antistatic agent is at least one of montmorillonite, polyacrylate and polyvinyl chloride.
9. A method for preparing an anti-aging and anti-sticking masterbatch for blow molding PE, characterized in that: Here are the steps: In the first step, the raw materials are weighed according to the weight ratio and introduced into a mixing device to mix the required raw materials; The second step is to pour the mixed raw materials into the extruder, so that the raw materials undergo heating, plasticization and extrusion processes to form masterbatch; The third step is to introduce the extruded masterbatch into the cooling equipment to quickly shape the masterbatch.
Citation Information
Patent Citations
Antistatic anti-aging polyethylene master batch and preparation method thereof
CN103881195A
PE anti-aging functional master batch
CN118496579A
Anti-aging flame-retardant master batch for PE artificial grass and preparation method of anti-aging flame-retardant master batch
CN118620307A